Early Sex Education and the Importance of Parents to Get Involved - Arifah Rasyidayanti; Luthfah Naily Faradisa; Tiara Diah Sosialita (Psikostudia : Jurnal Psikologi, 2023)
Children who are supposed to get protection and feel safe during their developmental period are still at risk of becoming victims of sexual violence. Sex education in early childhood has an important role in reducing the risk of sexual violence. The main providers of sex education for children are parents. The subjects in this study were 60 parents of "X" Surabaya Kindergarten students. This study used a quasi-experimental method with a one-group pretest-posttest design. This study will conduct a Wilcoxon test to measure the difference between pre and posttest. The effect size of this study will be conducted to measure the effectiveness of psychoeducation. These tests will be performed with Jamovi 2.3.18. The effectiveness of this psychoeducation was measured by a knowledge questionnaire on issues of sexual violence and early childhood sex education. Based on the results of the analysis, it was found that there was an increase in the participants' knowledge and there was a significant difference between the pretest and posttest results of 0.011 (sig. <0.05). Psychoeducation of early childhood sex education has a major impact on increasing parental understanding as indicated by an effect size value of 0.791. It can be concluded that parents' understanding of early childhood sex education can increase with psychoeducation.Anak-anak yang seharusnya mendapatkan perlindungan dan merasa aman selama masa perkembangannya masih berisiko untuk menjadi korban kekerasan seksual. Edukasi seks pada anak usia dini memiliki peranan penting untuk mengurangi risiko kekerasan seksual. Pemberi edukasi seks utama pada anak adalah orangtua. Subjek dalam penelitian ini adalah 60 orangtua TK “X” Surabaya. Penelitian ini menggunakan metode kuasi eksperimental dengan one-group pretest-postest design. Penelitian ini akan melakukan uji beda Wilcoxon untuk mengukur perbedaan pemahaman orangtua sebelum dan sesudah diberikannya psikoedukasi. Uji efektivitas juga dilakukan untuk mengukur efektivitas psikoedukasi yang dilakukan. Uji-uji ini akan dilakukan dengan Jamovi 2.3.18. Efektivitas psikoedukasi ini diukur dengan kuesioner pengetahuan mengenai isu kekerasan seksual dan edukasi seks usia dini. Berdasarkan hasil analisis, diketahui terdapat peningkatan pada pengetahuan peserta dan terdapat perbedaan yang signifikan antara hasil pretest dan posttest sebesar 0,011 (sig. <0,05). Psikoedukasi pendidikan seks usia dini memiliki dampak yang besar kepada peningkatan pemahaman orangtua yang ditunjukkan dengan nilai effect size sebesar 0,791. Dapat disimpulkan bahwa pemahaman orangtua terkait pendidikan seks usia dini dapat meningkat dengan adanya psikoedukasi.